2020
DOI: 10.17159/wsa/2020.v46.i2.8237
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring access to water for food production by emerging farmers in South Africa: What are the missing ingredients?

Abstract: One of the key components essential to the productivity of small-scale farmers who secured farms through the land redistribution programme in South Africa is access to reliable sources of water for irrigation. In this study, we deployed a stakeholder-oriented qualitative research methodology to understand the extent to which land reform farming schemes in Bela-Bela and Greater Sekhukhune have been able to access water and use it to enhance their agricultural production. We were keen to identify and articulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…While the restitution of agricultural land has been slower than intended, the reallocation of water has not always kept pace with the transfer of such land. In some instances, the previous owners traded away their existing lawful water-use rights, so that water allocation was not transferred to land reform beneficiaries (Chikozho et al, 2020). Furthermore, the Department of Economic and Social Affairs (ECOSOC) ( 2008) argues that there are other considerable challenges and impediments to the attainment of water sustainability as set out by the Millennium Development Goals (MDGs), the New Partnership for African Development (NEPAD), and above all by the underlying obligations set out in the Constitution of South Africa of equitable supply of water.…”
Section: The Flaws In the Policies And Strategies Towards Achieving Water Security In South Africamentioning
confidence: 99%
“…While the restitution of agricultural land has been slower than intended, the reallocation of water has not always kept pace with the transfer of such land. In some instances, the previous owners traded away their existing lawful water-use rights, so that water allocation was not transferred to land reform beneficiaries (Chikozho et al, 2020). Furthermore, the Department of Economic and Social Affairs (ECOSOC) ( 2008) argues that there are other considerable challenges and impediments to the attainment of water sustainability as set out by the Millennium Development Goals (MDGs), the New Partnership for African Development (NEPAD), and above all by the underlying obligations set out in the Constitution of South Africa of equitable supply of water.…”
Section: The Flaws In the Policies And Strategies Towards Achieving Water Security In South Africamentioning
confidence: 99%
“…Therefore, there are significant variations in former homelands' agricultural productivity due to inequalities in the distribution of natural resources, impacting household food security [11]. Thus, the need for equitable access to productive assets highlights the fact that without access to water and land resources, the poor will always have less economic flexibility and opportunities and will always remain vulnerable, not only to economic pressures but also to issues related to basic human rights [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This is evident in former homelands where smallholder farmers abandon farming to explore other alternative sources of income in urban areas. However, a key component of rural development in any society is access to land suitable for agriculture and water for irrigation by smallholder farmers who have always remained disadvantaged [10,13]. The consequence has seen the poor perpetually remain immersed in the poverty cycle, which prevents them from building the social capacity necessary to implement public participation in water resource management [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Closer analysis of the published literature shows that there have been very few studies done in South Africa that acknowledge the link between land and water even though this connection may seem self-evident. For instance Merrey et al (2009) demonstrated how monopoly and extreme inequity in ownership and access to water in the Olifants Catchment created artificial water scarcity for emerging farmers; Liebrand et al (2012) argue that in spite of its explicit focus on equity, the National Water Act (Act 36 of 1998;RSA, 1998) did little to bring about a more just allocation and use of water and, as a result, access to both land and water in South Africa continues to be concentrated in the hands of a privileged few, and is highly skewed along racial lines. It is our contention that such studies enable analysts to get a better grasp of how emerging farmers may gain access and use water in practice to make their farms more productive.…”
Section: Introductionmentioning
confidence: 99%